Mātauranga Māori and secondary science teaching: 2022 - Georgina Stewart (New Zealand Journal of Teachers' Work)
This reflection piece is written for secondary science teachers in Aotearoa New Zealand who are , for the first time, being obliged to consider the inclusion of Māori words and concepts in the NCEA achievement standards they use to assess their students. My aim is to unpack the issues implicit in the current trends to incorporate Māori knowledge in the secondary science curriculum, and help science teachers see the new standards in a more balanced and optimistic way.